Soil type, vegetation cover and temperature determinants of the diversity and structure of dung beetle assemblages in a South African open woodland and closed canopy mosaic. (22nd December 2021) - Daniel, Gimo M.; Noriega, Jorge Ari; da Silva, Pedro G.; Deschodt, Christian M.; Sole, Catherine L.; Scholtz, Clarke H.; Davis, Adrian L. V.
Abstract: Regional biogeographical patterns result from a complex combination across habitat, climate and environmental variables. Biotic and abiotic variables strongly influence the diversity and spatial distribution patterns. However, very few studies analyse the close interaction and effect of environmental variables on diversity at fine spatiotemporal scales. In this study, we evaluated the influence of soil type, vegetation cover and temperature on species diversity and functional structure of dung beetle assemblages. Dung beetle species were sampled using pitfall traps baited with cattle dung from sandy and clay soils in open woodland and closed canopy areas in Mkhuze Game Reserve, KwaZulu‐Natal, South Africa. We performed a PERMANOVA, a PERMDISP and an NMDS to analyse differences in species composition between soil and vegetation cover types. To test the effect of environmental variables on species richness and abundance, we performed a generalised least squares model. Lastly, we searched for nodes using a bipartite analysis to evaluate network's potential modularity. We collected 1439 specimens comprising 27 species and 13 genera. Species composition differed between environmental variables. Soil type was the most important driver for changes in dung beetle species composition. Species richness and abundance were influenced by the interaction between soil type and vegetation cover. The combination of microenvironmental preferences potentially influenced the dung beetle assemblage diversity and functional structure. Combining all these preferences may act as a dilution mechanism of interspecific competition in saturated habitat conditions, reducing the number of species that potentially interact and generating a modular network structure of the assemblage. Abstract : In this study, we evaluate the influence of soil type, vegetation cover and temperature on species diversity and functional structure of dung beetle assemblages. Resumo: Os padrões biogeográficos regionais resultam de uma combinação complexa de habitats, clima e variáveis ambientais. Variáveis bióticas e abióticas influenciam fortemente os padrões de diversidade e distribuição espacial. No entanto, poucos trabalhos analisam a interação e o efeito das variáveis ambientais na diversidade numa escala espacial e temporal fina. Nesse trabalho, avaliamos a influência do tipo de solo, cobertura da vegetação e temperatura na diversidade e estrutura funcional de uma assembleia de besouros rola‐bostas. As espécies de besouros rola‐bostas foram coletadas usando armadilhas de queda iscadas com fezes de bovinos em solos arenosos e argilosos em vegetação aberta e fechada na Reserva de Mkhuze, KwaZulu‐Natal, África do Sul. Usamos PERMANOVA, PERMDISP e NMDS para analisar a diferença na composição das espécies entre os tipos de solos e tipos vegetacionais. Para testar o efeito de variáveis ambientais sobre a riqueza das espécies e abundância utilizamos modelos generalizados de quadrados mínimos. Por último, usamos a análise bipartida para avaliar a modularidade potencial da rede. Foram coletados 1439 espécimes pertencentes a 27 espécies e 13 gêneros. A composição das espécies diferiu entre as variáveis ambientais. O tipo de solo foi o fator mais importante para as mudanças na composição das espécies de besouro rola‐bostas. A riqueza e abundância de espécies foram influenciadas pela interação entre o tipo de solo e a cobertura vegetal. A combinação de preferências microambientais potencialmente influenciou a diversidade da assembleia de besouros rola‐bostas e a estrutura funcional. A combinação de todas essas preferências pode atuar como um mecanismo de diluição da competição interespecífica em condições de habitat saturado, reduzindo o número de espécies que potencialmente interagem e gerando uma estrutura de rede modular da assembleia.